Factors influencing students voting behaviour: pre and post IIUM students’representatives council’s election 2014 - Omar, Muhamad Fuzi; Othman, Muhammad Hanif (Post Academic Publications, 2015)
The objectives of the study are to identify and rank the factors that influence students’ voting behavior before and after the International Islamic University Students’ Representative Council election, 2014. The data are collected using survey questionnaires. First, this study is conducted by focusing on students at International Islamic University Malaysia (IIUM) prior to the students’ representative council election 2014. The numbers of respondents are 206 students for pre-election survey and 230 students for post election survey. The methodologies used are descriptive statistics, factor analysis and non-parametric techniques using Kruskal- Wallis test. The results from factor analysis show four new factors which influence students’ voting behavior for pre IIUM SRC election 2014. Those factors are being labeled as 1) Manifesto, 2) Group Affiliation, 3) Candidates and 4) Status-Qua. However, for post IIUM SRC election 2014, three new factors have been constructed which are 1) Candidate and direct manifesto, 2) Group Affiliation and 3) Indirect manifesto.